Carbon nitride films grown by cathodic vacuum arc for hemocompatibility applications (2014)
Amorphous carbon nitride films have been obtained by pulsed cathodic arc at substrate temperatures of 20, 100, 150 and 200 °C. Film structure was investigated by Fourier Transformed infrared spectroscopy (FTIR) and Raman spectroscopy. Nitrile bands at approximately 2200 cm-1 were identified in all films. As the temperature increased a reduction in the concentration of sp3 bonds and a decrease in the structure disorder were observed. The relative intensity ratio of Raman D and G bands increased as the substrate temperature increased from 20 to 100°C. Nevertheless, at a critical temperature of 150°C, this trend was broken, and the film became amorphous. A peak at approximately 1610 cm-1 of films grown at 100°C, 150°C and 200 °C suggests that CNx is dominated by a relatively ordered graphite ring like glassy carbon. Moreover, the film grown at 150 °C presented the lowest roughness and the highest hardness and hemocompatibility.